1993
DOI: 10.1080/00039896.1993.9940364
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire Data as Predictors of Urinary Cotinine Levels among Nonsmoking Adolescents

Abstract: The strength of association between urinary cotinine and questionnaire data on passive smoking among 542 adolescents was evaluated. There were 103 individuals with urinary cotinine higher than 30 ng/ml; they were compared with all other subjects. The single variable that best predicted the urinary cotinine level was maternal smoking. A strong effect was made by house size and, consequently, house crowding. Maternal smoking and house crowding had a synergic effect. The subject's perception of passive smoking at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 17 publications
3
17
0
Order By: Relevance
“…Households with a higher socio-economic status can afford to buy or rent larger houses or flats and are more likely to be nonsmoker households. A negative correlation between children's urinary cotinine levels and house size was also reported in two other studies (Forastiere et al, 1993;Dell'Orco et al, 1995). When limiting the analysis to smoking households, the negative association between size of flat and children's CCR persists, indicating a higher degree of ETS dilution in larger flats.…”
Section: Etssupporting
confidence: 67%
See 2 more Smart Citations
“…Households with a higher socio-economic status can afford to buy or rent larger houses or flats and are more likely to be nonsmoker households. A negative correlation between children's urinary cotinine levels and house size was also reported in two other studies (Forastiere et al, 1993;Dell'Orco et al, 1995). When limiting the analysis to smoking households, the negative association between size of flat and children's CCR persists, indicating a higher degree of ETS dilution in larger flats.…”
Section: Etssupporting
confidence: 67%
“…Smoking at home explains almost 40% of the variability of the CCR and similar observations have been made in many earlier studies with preschool or school children (Jarvis et al, 1985(Jarvis et al, , 1987Coultas et al, 1987;Forastiere et al, 1993;Cook et al, 1994;Dell'Orco et al, 1995;Bono et al, 1996;Jordaan et al, 1999;Scherer et al, 1999). In a study carried out in Scotland, the number of smokers in the household Exposure of children to ETS Scherer et al accounted for as much as 51% of the observed variance in saliva cotinine (Jarvis et al, 1992).…”
Section: Etssupporting
confidence: 64%
See 1 more Smart Citation
“…Only adolescents who never smoked at T1 were included in this study. Assessing smoking among adolescents by self-reports showed to be valid (Barnea et al 1987;Forastiere et al 1993), and the instrument used in the present study has been used in various health studies in the Netherlands Harakeh et al 2004;Van De Ven et al 2006). …”
Section: Smoking Behaviormentioning
confidence: 99%
“…However, studies have shown that self-reports on smoking are reliable and valid when anonymity is guaranteed (Barnea et al 1987;Forastiere et al 1993), and prevalence estimates of smoking were similar when using self-reports or a biological markers (salivary cotinine) (Dolcini et al 2003). On the other hand, this has not been examined in adolescents with asthma.…”
Section: Strengths and Limitationsmentioning
confidence: 99%